Synthesis of Isoxazolidine-Fused Eight-Membered Heterocycles via an Intramolecular Nitrone–Alkene Cycloaddition - Zhu, Tong; Xiang, Jinbao; Liu, Zhenyu; Dang, Qun; Bai, Xu (Synlett, 2015)
An intramolecular nitrone–alkene cycloaddition yielded novel tricyclic eight-membered ring with a cis-fused isoxazolidine in good to excellent yields under mild reaction conditions.
Keywords: 1,3-dipolar cycloaddition; diastereoselectivity; fused-ring systems; eight-membered ring; isoxazolidine